INNOVATIVE SMES IN THE GLOBALISED ECONOMY - Chistruga, Boris (SWorldJournal, 2023)
The current stage of development of the world economy places new demands on all economic units, but particularly on transnational corporations and small and medium-sized enterprises. Globalisation supports and promotes innovative enterprises, whether larg